Mapping of azimuths of polarization of laser microscopic images of histological sections of human organs in the differentiation of poisoning by ethanol and carbon monoxide - Ivaskevych, I. B.; Bachynskyy, V. T.; Vanchulyak, O. Y.; Palyvoda, O. H. (Modern medical technology, 2019)
Purpose of the study. This work is aimed at research and substantiation of information possibilities of objective method of polarization mapping of microscopic images of histological sections of human biological tissues for the establishment and differentiation of С2Н5ОН and CO poisoning. Materisls and methods. Native histological sections of the brain, myocardium and adrenal glands from ethanol poisoning (n = 30) and CO (n = 20) were investigated using a laser polarimeter of standard scheme. Subsequently, statistical processing of the obtained results was conducted. Results. Statistical moments of 1–4th order were determined by the method of polarization mapping of microscopic images of histological sections of human biological tissues. The values of the statistical moments of the 1–4th order for brain tissue for С2Н5ОН and CO poisoning reach differences by 2–2,5 times, for myocardial tissue – 2,2–2,9 times, the adrenal glands – 1,4–1,8 times. Accordingly, the statistical moments of the 3rd and 4th order are more sensitive to the detection and differentiation of poisons, whereby the accuracy of the method of differential diagnosis of poisoning С2Н5ОН and CO reaches an adequate level (~ 90%) in the study of histological sections of the myocardium and brain. Conclusion. The obtained results show that the method of polarization mapping of microscopic images of human biological tissues gives an objective possibility of reliable establishment and differentiation of С2Н5ОН and СО poisoning.